A Comparison of Actigraphy and Sleep Diaries for Infants’ Sleep Behavior - Hall, Wendy A.; Liva, Sarah; Moynihan, Melissa; Saunders, Roy (Frontiers in Psychiatry, 2015)
Detecting the effectiveness of behavioral interventions to reduce infant night-waking requires valid sleep measures. Although viewed as an objective measure, actigraphy has overestimated night-waking. Sleep diaries are criticized for only documenting night-waking with infant crying. To support potential outcome measure validity, we examined differences between sleep diaries and actigraphy in detecting night-waking and sleep duration. We recruited 5.5 to 8-month-old infants for a behavioral sleep intervention trial conducted from 2009 to 2011. Intervention (sleep education and support) and control groups (safety education and support) collected infant diary and actigraphy data for 5 days. We compared night-time sleep actigraphy with diary data at baseline (194 cases), and 6 weeks (166 cases) and 24 weeks post-education (118 cases). We hypothesized numbers of wakes and wakes of ≥20 min would be higher and longest sleep time and total sleep time shorter by actigraphy compared with diaries. Using paired t-tests, there were significantly more actigraphy night wakes than diary wakes at baseline (t = 29.14, df = 193, p < 0.001), 6 weeks (t = 23.99, df = 165, p < 0.001), and 24 weeks (t = 22.01, df = 117, p < 0.001); and significantly more night wakes of ≥20 min by actigraphy than diary at baseline (t = 5.03, df = 183, p < 0.001), and 24 weeks (t = 2.19, df = 107, p < 0.05), but not 6 weeks (t = 1.37, df = 156, n.s.). Longest sleep duration was significantly higher by diary than actigraphy at baseline (t = 14.71, df = 186, p < 0.001), 6 weeks (t = 7.94, df = 158, p < 0.001), and 24 weeks (t = 17.18, df = 114, p < 0.001). Night sleep duration was significantly higher by diary than actigraphy at baseline (t = 9.46, df = 185, p < 0.001), 6 weeks (t = 13.34, df = 158, p < 0.001), and 24 weeks (t = 13.48, df = 114, p < 0.001). Discrepancies in actigraphy and diary data may indicate accurate actigraphy recording of movement but not sleep given active infant sleep and self-soothing.